Regulation of worker egg laying by larvae in a fission-performing ant. (August 2015) - Villalta, Irene; Angulo, Elena; Devers, Séverine; Cerdá, Xim; Boulay, Raphaël
Abstract : Ants provide one of the best examples of the division of labour in animal societies. In many species, although workers still have ovaries, they refrain from laying (haploid) eggs when a queen is present in the colony and, instead, dedicate themselves exclusively to domestic tasks. In monogynous species, workers generally begin laying eggs once the queen dies, which allows the colony's remaining resources to be invested in the workers' offspring. However, we found that in the fission-performing ant Aphaenogaster senilis, worker reproduction was also inhibited by brood pheromones; the presence of larvae, irrespective of their ploidy or origin, inhibited egg laying by orphaned workers in a dose-dependent manner. The end result was that workers allocated resources to the larvae that were present in the colony before starting to lay their own eggs. We also found that, while the number of workers reared was proportional to the number of larvae provided, the number of queens reared tended to plateau at six, regardless of the number of totipotent larvae present. This finding concurs with what has been observed in colonies in the field and fits with what the theory of local resource competition predicts. One explanation is that one of the queens produced is likely to mate and replace her dead mother as the head of the colony. Therefore, by rearing the queen's brood after her death, workers may have an opportunity to prolong the life of the colony. Highlights: Developmental plasticity allows ant larvae to develop into either queen or worker. Queen pheromones prevent larval development into queen. Workers do have ovaries but refrain from laying eggs in queenright colonies. Larval pheromones delay the onset of orphan worker egg laying. Rearing new queen from existing larvae allows colonies to survive queen death.